Religious Tourism to the Grave of Kyai Faqih as a Tourist Attraction - Addamawi, Daud Hizbalhaq; Mahendra, Maulana Iqbal; Pratama, Andryan Verly Dwi; Nadiah, Putri; Okta, Diah (CV. Sekawan Siji, 2025)
Kyai Haji Abdullah Faqih who is the inventor of the endog-endogan tradition in Banyuwangi. Kyai Abdullah Faqih was born in 1870 AD. According to the results of an interview with (great-grandson of Kyai Faqih Gus Reza) Kyai Faqih was born in 1873 in Pakis Hamlet, Balak Village. Kyai Haji Abdullah Faqih with his nickname Raden Mas Mudasir. Raden Mas Mudasir is a creative figure, actively studying the Quran since childhood, and likes to travel to seek knowledge (Jihad). He was born to Kyai Mangun Rokso and Nyai Rokso who were the fifth of seven siblings. In 1887, at that time Mudasir was still nine years old. He had decided to travel to seek knowledge to several Islamic boarding schools. One of them is at the Kyai Mangunrokso Islamic boarding school in Lumajang. After finishing in Lumajang, he continued to the pondok of Mbah Wali Sidiq Pasuruan. After Pasuruan, he continued to Bangkalan, in Bangkalan he shared a room with several scholars, namely K.H Hasyim Asyari, KH. Ma'ruf, KH. Manaf, and KH. Munawir Krapyak. They were all called the Pandawa Lima, because they were close friends. After that, from Bangkalan, he continued his studies to Semarang, then continued to the Mbah Jamil Buntet Islamic boarding school. Not only that, he sought knowledge directly in Mecca for 15 years. With the provision of knowledge, spirituality, mentality, experience, and the network of Nusantara scholars that had been established. After 15 years he returned in the 1900s, Kyai Faqih was encouraged to pioneer an Islamic boarding school in his village which became the beginning of Islamic boarding schools in Banyuwangi. And his first students came from the Osing area. He started this business in 1911, although he only obtained legality from the Dutch East Indies Government on August 17, 1917. However, the implementation of the Teacher Ordinance became an administrative challenge that often hampered the growth of Islamic boarding schools at that time. In 1900-1950, Kyai Faqih's works began to be numerous and widespread, one of which was endhog-endhogan or what is now known as Kembang Endhog. This traditional media of kembang endhog is a form of Kyai Faqih's struggle against the Dutch colonialists in Banyuwangi . He also fought back with art through endhog-endhogan which was spread by his students who at that time were studying at the pondok, as for the meaning of the endhog-endhogan tradition. White means Islam (faith in Allah SWT), the shell means protecting our Islam, yellow means ihsan (doing good in 3 things, namely the relationship between humans and God, the relationship between humans and humans and nature) this endhog flower must be stuck in a banana tree, because the banana tree has the meaning that once it bears fruit, the tree immediately dies, this can be interpreted that we as humans must be useful to others while we are alive. In addition, during his studies in Mecca, he collected several items, one of which was the lontar rengganis, and he also wrote works such as the Lontar Pandawa etc. which are still stored in the Islamic Boarding School. Not only that, many of his students became NU Banyuwangi Leaders at that time. He died on June 5, 1953 at the age of 83, buried next to his wife's grave which is next to the mosque of the Islamic boarding school he founded. The historical research method is also called the historical method, the method itself is a way, instruction, and implementation or technique to achieve a desired goal in making this research. According to the stages of the steps taken throughout the procedure, historical methods are divided into five groups, namely topic selection, source collection (HEURISTICS), source criticism (VERIFICATION), source interpretation (INTERPRETATION), and the last is writing (HISTORIOGRAPHY).